Well-posedness and stability for fuzzy fractional differential equations - Zhang, Xuping; Xi, Yanli; O’Regan, Donal (Nonlinear Analysis: Modelling and Control, 2022)
In this article, we consider the existence and uniqueness of solutions for a class of initial value problems of fuzzy Caputo–Katugampola fractional differential equations and the stability of the corresponding fuzzy fractional differential equations. The discussions are based on the hyperbolic function, the Banach fixed point theorem and an inequality property. Two examples are given to illustrate the feasibility of our theoretical results.
Keywords: fuzzy fractional differential equations; hyperbolic function; Banach fixed point theorem